Applicability of Accurate Ground Motion Estimation Using Initial P Wave for Earthquake Early Warning - Wang, Zijun; Zhao, Boming (Frontiers in Earth Science, 2021)
Earthquake early warning (EEW) system is capable of mitigating seismic hazards and reducing deaths, injuries, and economic losses. Although EEW approaches have already been developed worldwide, how to improve the accuracy and applicability is still controversial. Aiming at the ground motion estimation using the initial P wave, we investigated 8 representative characteristic parameters, i.e. the peak measurements and integral quantities, using the database of the 2008 Wenchuan earthquake, where the aftershocks with the criteria that 4.0 ≤ Ms ≤ 6.5 and epicentral distance less than 150 km are analyzed. We established the relationships between the 8 characteristic parameters and 4 ground motion parameters respectively, based on which the estimate accuracy and reliability and to what an extent the increasingly expanding time windows could affect the estimates are analyzed accordingly. We found that the integral quantities could also be a robust estimator for peak ground acceleration (PGA), peak ground velocity (PGV) and spectral intensity (SI), while the peak measurement is more useful in estimating peak ground displacement (PGD). In addition, for estimating the ground motion of events with magnitudes less than 6.5, a 2-second window could effectively improve the estimation accuracy by approximately 11.5-18.5% compared with using a 1-second window, as the window increases to 3-second, the accuracy would further improve while the growth rate will be reduced to around 3.0-8.0%.